ASUHAN KEPERAWATAN PADA ANAK DENGAN DIAGNOSA GASTROENTERITIS - astri doris (Akper Kesdam I/Bukit Barisan Padang, 2019)
Gastroenteritis is an inflammation of the stomach and intestines which is caused by various bacteria, viruses and pathogenic parasites. Gastroenteritis is also an inflammation that occurs in the stomach, small intestine, large intestine, which is caused by an infection of food containing bacteria or viruses which gives more frequent symptoms of diarrhea with a watery consistency and sometimes accompanied by nausea and vomiting. The danger of gastritis, if allowed to continue, will damage the function of the stomach and can increase the risk of gastric cancer and cause death. The purpose of this study was to determine how the application of nursing care to gastroenteritis patients. The research design used is a case study and descriptive research type. The research results were obtained in An. S complained of stomach pain, heartburn, nausea and dizziness.